(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Seaweed (sea weeds) is a fishery product that is not in the form of fish, but in the form of plants. The potential for seaweed as a non-oil and gas export commodity has bright economic prospects, to be cultivated both from the aspect of cultivation and business opportunities. This study aims to determine the role of post-harvest technology on the level of income of seaweed farmers. This research was conducted in Sapolohe, Bonto Bahari District, Bulukumba Regency, South Sulawesi, Indonesia with a total of 13 respondents who were selected by purvosive sampling method. The average income of respondent farmers using post-harvest technology is Rp. 9,160,000 and non-technologically Rp. 4,760,000. From the research it was concluded that the use of post-harvest technology on seaweed provides twice as much income compared to not using post-harvest technology.